We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
163
1
avatar+480 

Given f(x)=2x^2+3x and g(x)=5x^2−2x−6 .

What is (f+g)(x) ?

 

​ 3x^2−5x−6 ​

 Mar 11, 2019
edited by Melody  Mar 11, 2019
edited by whosmans  Mar 11, 2019
 #1
avatar+7712 
+2

\(f(x) = 2x^2 +3x\\ g(x) = 5x^2 - 2x - 6\\ (f + g)(x) = 7x^2 + x - 6\)

The function you typed with your question is \((g - f)(x)\).

 Mar 12, 2019

9 Online Users